Occupational Safety And Health (OSH) Towards Environment Mainstream Tool Practices (EMT) At Malaysia Small And Medium Manufacturing Sector - Abdullah, Norida; Hussin, Hanipah; Khoo, Nee Kah (Istanbul Kültür University, 2018)
Implementation OSH is so important in Malaysia workplace, especially in Small and Medium (S&M) Melaka manufacturing sector,In this paper,we would like to include the New Strategic practices such as a new parameter in order to improve the number of percentage of accident and improve environment issue in work place.There are four components such as understanding,commitment,practice and behavior will influence the improvement of this research towards green environment practices.Primary data from 20 S & M manufacturing sector in Melaka was taken through phone call interview survey on 14/12/17-15/01/2018.These 20 manufacturing sector been identify poor in managing their OSH and environmental.These research high light the problems in the Melaka manufacturing sector such as the high occupational accidents including environment issue, which are probably due to lack of non-compliance of the requirements of Occupational Safety and Health Act (OSHA) 1994,Environmental Quality Act 1974( EQA)and Guided Self Regulation Environmental Mainstream Tools (EMT).This study is to promote several management practices such training and safety management,understanding on self-regulation,enforcement and auditing towards EMT practices from the analysis we found that with good compliance will reduce the accident case at work place.